A model for stable isotopes of residual liquid water and ground ice in permafrost soils using arbitrary water chemistries and soil‐specific empirical residual water functions. (21st July 2020) - Fisher, David A.; Lacelle, Denis; Pollard, Wayne; Faucher, Benoit
Abstract: We present the basic theory of stable isotopes (δ( 18 O) and δ(D)) of freezing water solutions in the environment set within a water isotope‐augmented version of FREZCHEM(V15). We validate this model with a couple of examples. The isotope‐capable FREZCHEM is simplified to run much faster using set‐piece initial chemistries to calculate the freezing temperature of the remaining water. The fast version is embedded in a semi‐empirical model for residual liquid water in sub‐zero soils. A uniform specific soil column is driven with a defined seasonal temperature wave. The co‐isotopes of the residual water and ice are calculated as a function of time and depth. The model is applied to clayey soils of the sort sampled in detail in a 10 (10 to 20 m) core suite from the Mackenzie Delta, Canada. The stable isotopes are compared to the model ones and the match is quite good except in the uppermost 2.5 m, where an upturn in the model δ( 18 O) curve is smaller. If the upper 2.5 m of icy soil is populated with "modern" water, and below by late glacial meltwater the size of the upturn in δ( 18 O) starting at 2.5 m is reproduced by the model.